Tamar's revenge : La venganza de Tamar - Molina, Tirso de, 1571?-1648 (Hispanic classics. Golden-Age drama., 1988)
The story comes from the Second Book of Samuel and tells of the incestuous passion of Amnon, David's eldest son, for his half-sister, Tamar and the subsequent murder of Amnon by his brother Absolom. Amnon's lust is set in the context of complementary passions of ambition and revenge, reflected in Absolom and Tamar respectively. The play explores King David's conflict between justice and mercy when confronted with these tragic events. It is a work of constantly changing perspectives in which tragedy and comedy, instead of being simply juxtaposed, are blended in a highly original way. Tirso's play is one of the earliest treatments of a theme that has continued to be an inspiration for such modern writers as the novelist Dan Jacobson in The Rape of Tamar and the dramatist Peter Shaffer in Jonadab . Spanish text with facing-page translation, commentary and notes.